Role and Impact of Biomedical Engineering Discipline for Developing Country Perspective (International Journal of Innovative Research in Computer Science & Technology, 2018)
For a developing and largely populated  country, it is quite difficult to solve all healthcare related issues using existing technology with  affordable cost and desired precision. Moreover, to  carry out biomedical research and design to  improve biomedical equipment, devices and  maintenance are usually very expensive. Thus, it is  imperative and possible to extent indigenous  technologies and raw materials for the research  activities to design and develop sustained biomedical  devices and equipment, artificial organ and tissue,  prosthetics and implants, image modalities and  healthcare related software at low-cost. Thus, the  research and study related to biomedical  engineering need to improve to understand the role  and impact of this subject as a discipline.
Keywords: Dengue fever; dengue virus (DenV); promoter; bioinformatics; NCBI; Bangladesh